PROBLEMATIKA DALAM PENERAPAN PASAL 285 KUHP DAN LAMANYA HUKUMAN YANG DIJATUHKAN TERHADAP SUBYEK HUKUM PELAKU - Marisa Syambira (Universitas 17 Agustus 1945 Samarinda, 2013)
ABSTRACTApplication of Article 285 of the Criminal Code by the judges in the criminal case No. 542 / Pid.B / 2002 / PN.Tgr is right, but the length of the sentence imposed by the judges regardless of the things that burden and lighten the punishment meted out to the perpetrators of the criminal act of rape. In connection with the criminal case who was sentenced for 3 years and 6 months, the authors argue that the punishment is very light.Attitude toward law enforcement criminal acts in violation of Article 285 of the Criminal Code is essentially active, because the criminal act regulated and Article 285 of the Criminal Code are punishable offenses relative complaint. The legal process in this case does not have to wait for a complaint. Although no complaints enough with the information or reports, law enforcement will act and process in accordance with applicable law. In this event the complaint is not intended demanding events, but to prosecute those who perform acts of violence or threats of violence to force a woman sleeps with him outside of marriage.